Efecto de dos tratamientos silvícolas en la estructura de ecosistemas forestales en Durango, México - Solís Moreno, Raúl; Aguirre Calderón, Óscar Alberto; Treviño Garza, Eduardo Javier; Jiménez Pérez, Javier; Jurado Ybarra, Enrique; Corral-Rivas, Javier (Instituto de Ecología, A.C., 2016)
This work was carried out to evaluate the effect of two silvicultural treatments on the composition and structure of forest ecosystems in the “Sierra de la Candela” (Mountain range) near Tepehuanes, Durango. The analysis was done comparing two experimental plots managed under different silvicultural practices, the first with thinning and the second using selective logging. Several neighborhood-based indices were used via the so-called “structural group of five trees” sampling method. The results obtained in the study show that the tree species mixture and diversity is greater in the plot where the selective logging was applied, compared to that treated by thinning. Both plots present a clumped spatial tree distribution. On the other hand, the size differentiation results were not significantly different in relation to the dimensional tree structure of the studied plots.